APAKAH JAMINAN KESEHATAN TERKAIT DENGAN PERILAKU FERTILITAS RISIKO TINGGI SEPERTI HALNYA FAKTOR SOSIODEMOGRAFI? - Novriadhy, Dian; Yazid, Muhammad (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2014)
The research aim is to explain the relationship of sociodemografic and health security to high-risk fertility behaviour. Parity, maternal age and birth interval are used as a criterion in determining the category of high-risk pregnancy. The age of first marriage, desired number of children, education level and health insurance are used as independen variables. This study was carried on quantitative approach and cross-sectionally held in Palembang during March to April 2014. A total of 124 intended-pregnancy of pregnant women interviewed while performing antenatal visits. Chi-Square analysis was used for interpretation. The results showed that an 80% of high-risk pregnancy taht occurs had single risk factor. The age of first marriage, desired number of children and health security was known had relationship to high-risk pregnancy. While, both education level was statistically insignificant differenciate the current high-risk pregnancy. It is necessary to conduct further research to examine the influnce of health security reform implementation to reproductive health development both in short term and long term effect.